2015
DOI: 10.1002/ajmg.b.32336
|View full text |Cite
|
Sign up to set email alerts
|

Brain calcification process and phenotypes according to age and sex: Lessons from SLC20A2, PDGFB, and PDGFRB mutation carriers

Abstract: Primary Familial Brain Calcification (PFBC) is a dominantly inherited cerebral microvascular calcifying disorder with diverse neuropsychiatric expression. Three causative genes have been identified: SLC20A2, PDGFRB and, recently, PDGFB, whose associated phenotype has not yet been extensively studied. We included in the largest published case series of genetically confirmed PFBC, 19 PDGFB (including three new mutations), 24 SLC20A2 (including 4 new mutations), and 14 PDGFRB mutation carriers, from two countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
2
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(121 citation statements)
references
References 19 publications
4
102
2
2
Order By: Relevance
“…The reason for including this group in our study and analysis is supported by the overall similarity in neurological presentation of these cases to genetically determined PFBC as there was no statistically significant difference in movement disorders and cognitive changes between PFBC and pseudohypoparathyroidism. There was a trend of higher frequency of hyperkinetic movement disorders in comparison to parkinsonism but that was not statistically significant features of these cases were quite like the cases with genetically confirmed mutations in SLC20A2 or PDGFRB [62].…”
Section: Pseudohypoparathyroidismmentioning
confidence: 74%
See 1 more Smart Citation
“…The reason for including this group in our study and analysis is supported by the overall similarity in neurological presentation of these cases to genetically determined PFBC as there was no statistically significant difference in movement disorders and cognitive changes between PFBC and pseudohypoparathyroidism. There was a trend of higher frequency of hyperkinetic movement disorders in comparison to parkinsonism but that was not statistically significant features of these cases were quite like the cases with genetically confirmed mutations in SLC20A2 or PDGFRB [62].…”
Section: Pseudohypoparathyroidismmentioning
confidence: 74%
“…It has been suggested that clinical features among the commonly reported mutations were psychiatric signs (72.7%, 76.5%, and 80% for PDGFB, SLC20A2, and PDGFRB, respectively), movement disorders (45.5%, 76.5%, and 40%), and cognitive impairment (54.6%, 64.7%, and 40%) [62].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the most frequent three categories are: psychiatric disturbances (mainly mood, psychotic or personality disorders), cognitive impairment (involving mainly memory and executive functions), and movement disorders (mainly extrapyramidal signs). 1 Patients may present other symptoms such as gait disorder, cerebellar syndrome, dysarthria, and rarely seizures. Cephalalgia and especially migraine are frequent circumstances allowing the identification of brain calcification.…”
Section: Primary Brain Calcification (Pbc)mentioning
confidence: 99%
“…Cephalalgia and especially migraine are frequent circumstances allowing the identification of brain calcification. 1 PBC is inherited as an autosomal dominant trait. In this context, causative variants have been identified in 4 genes: SLC20A2 (OMIM 158378), 2 PDGFRB (OMIM 173410), 3 PDGFB (OMIM 190040), 4 and XPR1 (OMIM 605237).…”
Section: Primary Brain Calcification (Pbc)mentioning
confidence: 99%
See 1 more Smart Citation